The Study of Acute Respiratory Distress Syndrome due to Strongyloides stercoralis in Lupus Nephritis - Umapati Hegde; Hardik Patel; Vipul Chakurkar (New Frontiers in Medicine and Medical Research Vol. 5, 2021)
Strongyloides stercoralis is an intestinal helminth that infects humans transdermally, endemic in tropical and subtropical rural regions. In immunocompetent subjects, the pulmonary disease caused by the parasite most commonly is asymptomatic to mild disease, but the same can be life-threatening in immunocompromised subjects. Twenty-one-year-old male suffering from class IV lupus nephritis was treated with steroids and Cyclophosphamide. After 1.5 months’ therapy, he presented with diarrhoea, abdominal pain, and dyspnoea, which rapidly worsened to acute respiratory distress syndrome (ARDS) needing ventilation. Bronchoalveolar lavage (BAL)showed Strongyloides stercoralis. He was treated with IV antibiotics, Ivermectin, and Albendazole with good results. In this article, the authors summarize a case of hyper infection syndrome of strongyloidiasis in immunosuppressed patients and discuss the various aspects of Strongyloides stercoralis infection, emphasizing the parasite’s life cycle and the treatment modalities. Corticosteroid administration can lead to the development of Strongyloides hyper-infection syndrome in endemic areas. Therefore, early suspicion, diagnosis, and treatment of Strongyloidiasis are needed to save life.